(untitled) (Research, Society and Development, 2020)
This work aims to gather and present a study on the routine of care for babies, as well as their main oral manifestations. Seeking to guide parents and professionals about oral hygiene, type of diet and posture in relation to harmful oral habits. Dental care for babies aged 0 to 36 months is of great importance for the assessment of their stomatognathic development. At this stage, it is necessary that those responsible have the necessary guidance on possible harmful habits, caries injuries, malocclusions, type of diet, breastfeeding and oral hygiene. The Dental Surgeon together with the Pediatric Dentist must be up to date and ready to pass on to those responsible a positive attitude of health promotion and awareness of dental care for babies. A literature review will be carried out through searches of articles published in the Google Scholar, Scielo and BVSalud.